A systematic review of responsible stewardship of research and health data from Indigenous communities - Alec J. Calac; Timothy K. Mackey (npj Digital Medicine)
Abstract There is growing recognition of the moral and legal authority of Indigenous Peoples to regulate research and other matters that involve their communities under the principle of Indigenous Data Sovereignty (IDS). This systematic review has two aims: (1) detail IDS considerations and practices in health research in the United States and other global contexts; and (2) identify frameworks that operationalize IDS practices for responsible conduct of research and use of data-driven technologies. Our review returned 41 relevant articles detailing specific considerations for the collection, access, and use of Indigenous data, and sub-themes such as cultural and regional considerations. More than half of the articles articulated a theoretical framework or detailed set of guidelines for using Indigenous data, with two especially focused on digital data considerations. Results indicate that intentional engagement with Indigenous researchers and communities will minimize harm and maximize benefits for all participating in research and technology development.